Pembelajaran Mufrodat pada Pelajar Tuli Menggunakan MMR dan Android di SLB B Karya Ibu Palembang - Ilham Solihin; Zulkipli Lessy (Departement of Mathematics Education, 2023)
The success of a learning activity is supported by the ability of students to build curiosity through appropriate learning methods. Learning for children with special needs when receiving and conveying information, they use sign language as a means of receiving and conveying information. A fixed and precise method is needed for deaf children. The researcher chose MMR